Para-aramid lithium battery diaphragm and preparation method thereof
By modifying para-aramid slurry and incorporating nano-ceramic composite materials and composite nano-solid materials, the thermal stability and solubility issues of para-aramid lithium battery separators were resolved, improving the tensile strength and heat resistance of the separators and ensuring the electrochemical stability and discharge capacity of the batteries.
Patent Information
- Application Number
- CN202511409671.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-29
- Publication Date
- 2026-01-09
AI Technical Summary
Existing para-aramid lithium battery separators suffer from insufficient thermal stability, mechanical property defects, and poor solubility under high-temperature conditions, failing to meet the stability requirements under high-power discharge or abnormal operating conditions.
Modified para-aramid slurry is used, and nano-ceramic composite powder and composite nano-solid materials are added. The tensile strength, heat resistance and solubility of the membrane are improved by copolymerization modification of the ether bond third monomer. The preparation method includes mixing, coating and drying processes.
It improves the thermal stability and mechanical properties of the separator, reduces the thermal shrinkage rate at high temperatures, enhances its solubility in polar solvents, and maintains the electrochemical stability and discharge capacity of the battery.
Smart Images

Figure BDA0005621013810000091 
Figure BDA0005621013810000101
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of battery materials, and in particular to a para-aramid lithium battery separator and a preparation method thereof. BACKGROUND
[0002] In a lithium ion battery, the separator, as a key component, bears the core functions of isolating the positive and negative electrodes to prevent short circuiting and ensuring smooth transmission of lithium ions, and its performance directly determines the safety, cycle life and energy density of the battery. Although the traditional polyolefin separator has certain mechanical properties, it is prone to rapid thermal contraction in a high-temperature environment, which may cause the positive and negative electrodes to contact and short circuit, and even lead to thermal runaway. Para-aramid is considered as an ideal material for high-safety lithium battery separators due to its high modulus, chemical corrosion resistance and excellent high-temperature resistance. However, the existing para-aramid lithium battery separator still has many technical bottlenecks in practical application. Firstly, the thermal stability is insufficient. Although the para-aramid itself has excellent heat resistance, the separator made of it still has a high longitudinal thermal shrinkage rate in a high-temperature environment, which cannot fully meet the stability requirements under high-power discharge or abnormal working conditions. Secondly, the mechanical properties are defective. The tensile strength of the separator is poor, and it is easy to be damaged due to mechanical stress during battery assembly and charge-discharge cycling, which affects the structural integrity of the battery. Thirdly, the material solubility is difficult. The para-aramid molecules have strong hydrogen bonding between them, and the solubility in conventional polar solvents is extremely poor, which makes it difficult to process and prepare. Therefore, how to overcome the problems of insufficient thermal stability, defective mechanical properties and poor solubility of the para-aramid lithium battery separator has become a key problem to be solved in the development of lithium ion battery separator technology. SUMMARY
[0003] In view of the deficiencies of the prior art, the present application provides a para-aramid lithium battery separator and a preparation method thereof.
[0004] In a first aspect, the present application provides a para-aramid lithium battery separator, which adopts the following technical solution: A para-aramid lithium battery separator, comprising para-aramid slurry and a base film, the para-aramid slurry being coated on both sides of the base film to form a para-aramid coating layer, the para-aramid slurry comprising the following raw materials in parts by weight: 20-40 parts of modified para-aramid polymer solution, 10-20 parts of nano-ceramic composite material powder, 10-18 parts of solvent. The nano-ceramic composite material powder comprises the following raw materials in parts by weight: 50-100 parts of nano-alumina, 8-12 parts of nano-zirconia, 0.3-0.8 parts of yttrium trioxide, 1-5 parts of magnesium nitrate hexahydrate, 0.1-1 parts of polyacrylic acid, 1-2 parts of ammonia water, 1-3 parts of coupling agent and 20-30 parts of silicon dioxide.
[0005] By adopting the technical scheme, the raw material is improved in the application, the nano ceramic composite powder is added, the nano ceramic composite powder can be uniformly dispersed in the para-aramid pulp, the bonding force between the para-aramid pulp and the base film is further enhanced, the strength and structural stability of the base film are prolonged, and therefore the tensile strength, heat resistance, compactness and structural stability of the diaphragm are further improved.
[0006] Further, the preparation method of the nano ceramic composite powder comprises the following steps: The nano zirconium dioxide, magnesium nitrate hexahydrate, polyacrylic acid and yttrium trioxide are mixed, the nano aluminum oxide is added and mixed, the ammonia water is added and mixed, centrifugation is performed, drying is performed, and the powder is obtained; The powder is once calcined to obtain the powder material; The powder material is twice calcined; The powder material after the twice calcination is mixed with the silicon dioxide and the coupling agent, centrifugation is performed, drying is performed, and the nano ceramic composite powder is obtained.
[0007] By adopting the technical scheme, the nano ceramic composite powder is prepared by mixing the nano aluminum oxide and the nano zirconium dioxide as main raw materials with yttrium trioxide, magnesium nitrate hexahydrate, polyacrylic acid and ammonia water, and then mixing the prepared mixture with silicon dioxide under the action of a coupling agent, centrifugation and drying, so that the nano ceramic composite powder containing nano aluminum oxide, nano zirconium dioxide and silicon dioxide is prepared, and therefore the tensile strength, heat resistance, compactness and structural stability of the diaphragm are further improved.
[0008] Further, when the powder is once calcined, the calcination temperature is 1100-1400 DEG C, and the calcination time is 1-3 hours.
[0009] Further, when the powder material is twice calcined, the calcination temperature is 1500-1700 DEG C, and the calcination time is 1.5-3.5 hours.
[0010] Further, before the powder material is twice calcined, the powder material is placed at 180-220 MPa for 5-15 minutes, and then pre-calcined at 1000-1200 DEG C for 0.5-1.5 hours.
[0011] Further, the nano ceramic composite powder further comprises 5-10 parts by mass of a composite nano solid material.
[0012] Further, the composite nano solid material comprises the following raw materials by weight: 15-20 parts of tetraethyl orthosilicate, 6-13 parts of ethanol, 1-5 parts of hydrochloric acid and 0.1-1 part of zirconium oxychloride.
[0013] By adopting the technical scheme, the raw material is improved, and the composite nano solid material is added, so that the composite nano solid material can be uniformly dispersed in the para-aramid pulp, thereby further improving the heat resistance, tensile strength, compactness and structural stability of the diaphragm.
[0014] Further, the preparation method of the composite nano solid material comprises the following steps: mixing tetraethyl orthosilicate, a first portion of ethanol and hydrochloric acid, adding zirconium oxychloride and a second portion of ethanol, mixing, drying, and crushing to obtain the composite nano solid material.
[0015] By adopting the technical scheme, the raw material is improved, and the composite nano solid material is added, so that the composite nano solid material can be uniformly dispersed in the para-aramid pulp, thereby further improving the heat resistance, tensile strength, compactness and structural stability of the diaphragm.
[0016] Further, the mass ratio of the first portion of ethanol and the second portion of ethanol is (5-10):(1-3).
[0017] Further, the preparation method of the modified para-aramid polymerization liquid comprises the following steps: The para-benzene dicarboxylic chloride, the para-phenylenediamine and the third monomer with a molar ratio of 10:(3-7):(3-7) are blended and dispersed in the composite solvent, and a modified para-aramid polymerization liquid is obtained by reaction.
[0018] Further, the third monomer comprises 4,4'-diamino diphenyl ether and adipic acid diamine, and the molar ratio of 4,4'-diamino diphenyl ether and adipic acid diamine is (6-7):(3-4).
[0019] Further, the composite solvent comprises chlorinated (1-butyl-3-methyl imidazole) ionic liquid, and the volume ratio of the chlorinated (1-butyl-3-methyl imidazole) ionic liquid is 13-18% of the total volume of the composite solvent.
[0020] By adopting the above technical solution, this application uses terephthaloyl chloride, p-phenylenediamine and a third monomer to prepare a modified para-aramid polymer solution. The third monomer includes 4,4'-diaminodiphenyl ether, which can reduce the reaction rate and avoid excessive aggregation of high molecular weight segments of para-aramid. Meanwhile, 4,4'-diaminodiphenyl ether can disrupt the regularity of the para-aramid molecular chain. The ether bonds (-O-) in its molecule disrupt the completely para-symmetrical structure of the para-aramid backbone. Compared with the rigid p-phenylenediamine-terephthaloyl chloride segments of pure para-aramid, the flexibility of the ether bonds causes local twisting of the molecular chain, reducing the regularity of the molecular chain arrangement. At the same time, the introduction of 4,4'-diaminodiphenyl ether makes the hydrogen bond distribution uneven, reduces the hydrogen bond density per unit volume, and weakens the intermolecular forces. Furthermore, when 4,4'-diaminodiphenyl ether is added to the system, the crystallinity of para-aramid decreases and the crystal region size shrinks, making it easier for the solvent to penetrate into the interior of para-aramid. After modification with 4,4'-diaminodiphenyl ether, the proportion of amorphous regions of the para-aramid polymer increases, and solvent molecules can diffuse in smoothly, forming a solvation layer and gradually dissolving the para-aramid. The ether bonds of 4,4'-diaminodiphenyl ether generate dipole-dipole interactions with the carbonyl groups in the composite solvent, significantly increasing the binding energy and improving the compatibility between the polymer and the solvent. Overall, 4,4'-diaminodiphenyl ether significantly improves the solubility of para-aramid fibers in composite solvents through a triple mechanism: disrupting molecular chain regularity, reducing crystallinity, and enhancing solvent interactions.
[0021] This application incorporates adipic acid diamine into the third monomer, introducing a flexible amide bond monomer, which breaks the regularity of the para-aramid molecular chain, improves its solubility in composite solvents, and maintains the mechanical strength of the battery separator.
[0022] The preparation method of this application effectively improves the solubility of para-aramid in polar solvents by copolymerizing and modifying the ether-bonded third monomer, while maintaining electrochemical stability. At the same time, the application of the ionic liquid complex solvent system effectively destroys the original intermolecular hydrogen bond network of para-aramid, reduces crystallinity, and utilizes the stacking effect to generate competition, thereby increasing the molecular chain spacing of para-aramid and providing channels for solvent molecule penetration. Therefore, the prepared separator does not affect the battery's discharge capacity, and the battery's cycle life is also guaranteed.
[0023] Secondly, this application provides a method for preparing a para-aramid lithium battery separator, which adopts the following technical solution: A method for preparing a para-aramid lithium battery separator, comprising the following steps: Weigh out each ingredient according to the formula; Modified para-aramid polymer liquid, nano-ceramic composite material powder, and solvent are mixed to obtain para-aramid slurry. The para-aramid slurry is then coated on both sides of the base film. After coagulation, washing, and drying, the para-aramid lithium battery separator is obtained.
[0024] In summary, this application includes at least one of the following beneficial technical effects: This application discloses a para-aramid lithium battery separator and its preparation method. In this application, by improving the raw materials of the para-aramid slurry and adding nano-ceramic composite material powder to the para-aramid slurry, the para-aramid separator has better thermal stability, reducing the phenomenon of thermal shrinkage of the separator at high temperature, thereby improving the electrochemical stability of the lithium battery. At the same time, the separator prepared by this application will not affect the discharge capacity and cycle life of the battery. Detailed Implementation
[0025] The technical solutions of this application are further illustrated by specific embodiments below. These specific embodiments do not represent a limitation on the scope of protection of this application. Any non-essential modifications and adjustments made by others based on the concept of this application still fall within the scope of protection of this application.
[0026] All raw materials involved in this application are commercially available products, among which, Nano-alumina, 99.9% purity, purchased from Aladdin; Nano-zirconia, 99.95% purity, purchased from Wuxi Tuoboda Titanium Dioxide Products Co., Ltd. Polyacrylic acid, purchased from Sinopharm Chemical Reagent Co., Ltd.; The present application will be further described in detail below with reference to embodiments and comparative examples.
[0027] Preparation Example 1: The preparation method of nano-ceramic composite powder includes the following steps: (1) Preparation of composite nanomaterials: 18 kg of tetraethyl orthosilicate, 7 kg of ethanol, and 3 kg of hydrochloric acid were mixed to obtain a mixed solution. The mixed solution was heated and refluxed at 65°C for 2 hours. Then, 0.5 kg of zirconium oxychloride and 1.5 kg of ethanol were added and mixed. The mixture was heated and refluxed for another 2 hours, then dried and pulverized to obtain a composite nano-solid material.
[0028] (2) Preparation of nano-ceramic composite powder: Mix 10 kg of nano-zirconia, 3 kg of magnesium nitrate hexahydrate, 0.5 kg of polyacrylic acid, and 0.5 kg of yttrium oxide, then add 75 kg of nano-alumina and mix. Stir the mixture while slowly adding 1.5 kg of ammonia water dropwise, and monitor the pH value in real time with a pH meter to maintain the pH at 9-10. After the addition is complete, continue stirring for 2 hours, centrifuge, and dry at 50°C for 20 minutes to obtain powder. The dried powder was calcined at 1280℃ for 2 hours to obtain the powder material. After the powder was held under pressure at 200 MPa for 10 minutes, it was pre-calcined at 1100℃ for 1 hour, then heated to 1600℃ at 100℃ / min and calcined again at 1600℃ for 2.5 hours to obtain the powder after secondary calcination. 25 kg of silica, 50 L of water, and 200 L of ethanol were mixed to obtain a silica emulsion. After the powder was calcined twice, it was mixed with silica emulsion and 2 kg of silane coupling agent KH-570, centrifuged, dried, and then 7 kg of composite nano solid material was added and mixed to obtain nano ceramic composite material powder.
[0029] Preparation Example 2: The preparation method of nano-ceramic composite powder includes the following steps: (1) Preparation of composite nanomaterials: 15 kg of tetraethyl orthosilicate, 5 kg of ethanol, and 1 kg of hydrochloric acid were mixed to obtain a mixed solution. The mixed solution was heated and refluxed at 65°C for 2 hours. Then, 0.1 kg of zirconium oxychloride and 1 kg of ethanol were added and mixed. The mixture was heated and refluxed for another 2 hours, then dried and pulverized to obtain a composite nano-solid material.
[0030] (2) Preparation of nano-ceramic composite powder: Mix 8 kg of nano-zirconia, 1 kg of magnesium nitrate hexahydrate, 0.1 kg of polyacrylic acid, and 0.3 kg of yttrium oxide, then add 50 kg of nano-alumina and mix. Stir the mixture while slowly adding 1 kg of ammonia water dropwise, and monitor the pH value in real time with a pH meter to maintain the pH at 9-10. After the addition is complete, continue stirring for 2 hours, centrifuge, and dry at 50°C for 20 minutes to obtain powder. The dried powder was calcined at 1280℃ for 2 hours to obtain the powder material. After the powder was held under pressure at 200 MPa for 10 minutes, it was pre-calcined at 1100℃ for 1 hour, then heated to 1600℃ at 100℃ / min and calcined again at 1600℃ for 2.5 hours to obtain the powder after secondary calcination. 20 kg of silica, 40 L of water, and 120 L of ethanol were mixed to obtain a silica emulsion. After the powder was calcined twice, it was mixed with silica emulsion and 1 kg of silane coupling agent KH-570, centrifuged, dried, and then 5 kg of composite nano solid material was added and mixed to obtain nano ceramic composite material powder.
[0031] Preparation Example 3: The preparation method of nano-ceramic composite powder includes the following steps: (1) Preparation of composite nanomaterials: 20 kg of tetraethyl orthosilicate, 10 kg of ethanol, and 5 kg of hydrochloric acid were mixed to obtain a mixed solution. The mixed solution was heated and refluxed at 65°C for 2 hours. Then, 1 kg of zirconium oxychloride and 3 kg of ethanol were added and mixed. The mixture was heated and refluxed for another 2 hours, dried, and pulverized to obtain a composite nano-solid material.
[0032] (2) Preparation of nano-ceramic composite powder: 12 kg of nano-zirconia, 5 kg of magnesium nitrate hexahydrate, 1 kg of polyacrylic acid, and 0.8 kg of yttrium oxide were mixed together, and then 100 kg of nano-alumina was added and mixed. The mixture was stirred while 2 kg of ammonia water was slowly added dropwise. The pH value was monitored in real time with a pH meter and maintained at 9-10. After the addition was completed, the mixture was stirred for 2 hours, centrifuged, and dried at 50°C for 20 minutes to obtain powder. The dried powder was calcined at 1280℃ for 2 hours to obtain the powder material. After the powder was held under pressure at 200 MPa for 10 minutes, it was pre-calcined at 1100℃ for 1 hour, then heated to 1600℃ at 100℃ / min and calcined again at 1600℃ for 2.5 hours to obtain the powder after secondary calcination. 30 kg of silica, 60 L of water, and 240 L of ethanol were mixed to obtain a silica emulsion. After the powder was calcined twice, it was mixed with silica emulsion and 3 kg of silane coupling agent KH-570, centrifuged, dried, and then 10 kg of composite nano solid material was added and mixed to obtain nano ceramic composite material powder.
[0033] Example 1: A method for preparing a para-aramid lithium battery separator, comprising the following steps: S1. Preparation of modified para-aramid polymer solution: Under nitrogen protection, 1-butyl-3-methylimidazolium chloride ionic liquid and DMAC were mixed at a volume ratio of 13:87 and stirred until homogeneous to obtain a composite solvent. Then, 7 mol of the third monomer (6 mol of 4,4'-diaminodiphenyl ether and 1 mol of adipate diamine) was added to the composite solvent and completely dissolved. Then, 3 mol of p-phenylenediamine was added and stirred until completely dissolved. The mixture was then cooled to -10°C. Finally, 10 mol of terephthaloyl chloride was added in three portions and stirred at 1000 r / min. When the viscosity of the system increased sharply, the cooling was stopped and the reaction was allowed to continue at room temperature for 2 h. Finally, calcium hydroxide was added to adjust the pH of the system to 7. After degassing with a vacuum pump, the modified para-aramid polymer solution was obtained.
[0034] S2. Preparation of para-aramid slurry: 30 kg of modified para-aramid polymer solution and 15 kg of nano-ceramic composite powder were mixed and stirred at 500 r / min for 30 min. Then, 14 kg of solvent (a composite of dimethylformamide and potassium chloride with a mass ratio of 1:0.5) was added and stirred at 500 r / min for 90 min to adjust the viscosity of the system to 2000 mPa·s. The mixture was then passed through a 350 mesh filter to obtain para-aramid slurry. The nano-ceramic composite powder was prepared according to Preparation Example 1.
[0035] S3. Preparation of battery separator: The para-aramid slurry was uniformly coated onto both sides of the base membrane using a coating machine. The membrane was then cured in a coagulation bath using an immersion-reverse method, washed with deionized water, and dried to obtain the para-aramid lithium battery separator.
[0036] Example 2: A method for preparing a para-aramid lithium battery separator, comprising the following steps: S1. Preparation of modified para-aramid polymer solution: Under nitrogen protection, 1-butyl-3-methylimidazolium chloride ionic liquid and DMAC were mixed at a volume ratio of 13:87 and stirred until homogeneous to obtain a composite solvent. Then, 7 mol of the third monomer (6 mol of 4,4'-diaminodiphenyl ether and 1 mol of adipate diamine) was added to the composite solvent and completely dissolved. Then, 3 mol of p-phenylenediamine was added and stirred until completely dissolved. The mixture was then cooled to -10°C. Finally, 10 mol of terephthaloyl chloride was added in three portions and stirred at 1000 r / min. When the viscosity of the system increased sharply, the cooling was stopped and the reaction was allowed to continue at room temperature for 2 h. Finally, calcium hydroxide was added to adjust the pH of the system to 7. After degassing with a vacuum pump, the modified para-aramid polymer solution was obtained.
[0037] S2. Preparation of para-aramid slurry: 20 kg of modified para-aramid polymer solution and 10 kg of nano-ceramic composite powder were mixed and stirred at 500 r / min for 30 min. Then, 10 kg of solvent (a composite of dimethylformamide and potassium chloride with a mass ratio of 1:0.5) was added and stirred at 500 r / min for 90 min to adjust the viscosity of the system to 2000 mPa·s. The mixture was then passed through a 350 mesh filter to obtain para-aramid slurry. The nano-ceramic composite powder was prepared in Preparation Example 2.
[0038] S3. Preparation of battery separator: The para-aramid slurry was uniformly coated onto both sides of the base membrane using a coating machine. The membrane was then cured in a coagulation bath using an immersion-reverse method, washed with deionized water, and dried to obtain the para-aramid lithium battery separator.
[0039] Example 3: A method for preparing a para-aramid lithium battery separator, comprising the following steps: S1. Preparation of modified para-aramid polymer solution: Under nitrogen protection, 1-butyl-3-methylimidazolium chloride ionic liquid and DMAC were mixed at a volume ratio of 13:87 and stirred until homogeneous to obtain a composite solvent. Then, 7 mol of the third monomer (6 mol of 4,4'-diaminodiphenyl ether and 1 mol of adipate diamine) was added to the composite solvent and completely dissolved. Then, 3 mol of p-phenylenediamine was added and stirred until completely dissolved. The mixture was then cooled to -10°C. Finally, 10 mol of terephthaloyl chloride was added in three portions and stirred at 1000 r / min. When the viscosity of the system increased sharply, the cooling was stopped and the reaction was allowed to continue at room temperature for 2 h. Finally, calcium hydroxide was added to adjust the pH of the system to 7. After degassing with a vacuum pump, the modified para-aramid polymer solution was obtained.
[0040] S2. Preparation of para-aramid slurry: 40 kg of modified para-aramid polymer solution and 20 kg of nano-ceramic composite powder were mixed and stirred at 500 r / min for 30 min. Then, 18 kg of solvent (a composite of dimethylformamide and potassium chloride with a mass ratio of 1:0.5) was added and stirred at 500 r / min for 90 min to adjust the viscosity of the system to 2000 mPa·s. The mixture was then passed through a 350 mesh filter to obtain para-aramid slurry. The nano-ceramic composite powder was prepared in Preparation Example 3.
[0041] S3. Preparation of battery separator: The para-aramid slurry was uniformly coated onto both sides of the base membrane using a coating machine. The membrane was then cured in a coagulation bath using an immersion-reverse method, washed with deionized water, and dried to obtain the para-aramid lithium battery separator.
[0042] Example 4: The difference from Example 1 is that the nano-ceramic composite powder was prepared in Example 2.
[0043] Example 5: The difference from Example 1 is that the nano-ceramic composite powder was prepared by Preparation Example 3.
[0044] Example 6: The difference from Example 1 is that the amount of nano-ceramic composite material powder added is 10 kg when preparing the para-aramid slurry.
[0045] Example 7: The difference from Example 1 is that the amount of nano-ceramic composite material powder added is 20 kg when preparing the para-aramid slurry.
[0046] Example 8: The difference from Example 1 is that the amount of composite nano solid material added is 5 kg when preparing nano-ceramic composite powder.
[0047] Example 9: The difference from Example 1 is that the amount of composite nano solid material added is 10 kg when preparing nano-ceramic composite powder.
[0048] Comparative Example 1: The difference from Example 1 is that no nano-ceramic composite material powder is added when preparing the para-aramid slurry.
[0049] Comparative Example 2: The difference from Example 1 is that the amount of nano-ceramic composite material powder added is 9 kg when preparing the para-aramid slurry.
[0050] Comparative Example 3: The difference from Example 1 is that the amount of nano-ceramic composite material powder added is 21 kg when preparing the para-aramid slurry.
[0051] Comparative Example 4: The difference from Example 1 is that no composite nanomaterials are added when preparing nano-ceramic composite powder.
[0052] Comparative Example 5: The difference from Example 1 is that the amount of composite nano solid material added is 4 kg when preparing nano-ceramic composite powder.
[0053] Comparative Example 6: The difference from Example 1 is that the amount of composite nano solid material added is 11 kg when preparing nano-ceramic composite powder.
[0054] Performance testing: 1. Tensile strength: The diaphragm samples obtained in the examples and comparative examples were cut into rectangular paper pieces with a specification of 20mm×50mm. Tensile strength tests were performed using a servo high and low temperature tensile testing machine with a tensile speed of 5mm / min and a gravity sensor specification of 500kN to detect their tensile strength.
[0055] 2. Heat shrinkage rate test: The diaphragm samples obtained in the examples and comparative examples were heat-treated in an oven at 130°C for 60 minutes, and the change in diaphragm area before and after heat treatment was measured.
[0056] 3. Discharge capacity: The separators obtained in the examples and comparative examples were assembled into CR2032 button batteries in the order of positive electrode active material, electrolyte, separator, and lithium sheet. The batteries were then pressed together using a battery packaging machine and left to stand for more than 12 hours until the batteries were fully balanced. The discharge capacity of the samples was then tested on a battery testing system to test the discharge capacity at 3C.
[0057] 4. Battery capacity retention rate: The separators obtained in the examples and comparative examples were assembled into CR2032 button batteries in the order of positive electrode active material, electrolyte, separator, and lithium sheet. The batteries were then pressed together using a battery packaging machine and left to stand for more than 12 hours until the batteries were fully balanced. After that, charge-discharge cycle tests were performed on a battery testing system with a constant current rate of 1C and a charge-discharge cutoff voltage of 2.5-3.8V. The battery capacity retention rate was recorded after 100 cycles.
[0058] Table 1 Performance Test Table As shown in Table 1, the para-aramid lithium battery separator prepared in this application has good thermal stability, reducing the thermal shrinkage of the separator at high temperatures and thus improving the electrochemical stability of the lithium battery. Secondly, this application effectively improves the solubility of para-aramid in polar solvents by copolymerizing and combining it with an ether-bonded third monomer, while maintaining electrochemical stability. The separator prepared in this application does not affect the discharge capacity of the battery, and the battery cycle life is also guaranteed.
[0059] Based on the test results of Example 1 and Comparative Example 1, it can be seen that the tensile strength and thermal shrinkage rate of Example 1 are better than those of Comparative Example 1. This indicates that the addition of nano-ceramic composite material powder in this application effectively improves the thermal stability of the separator and effectively reduces the thermal shrinkage of the separator at high temperatures, thereby improving the electrochemical stability of the lithium battery. At the same time, the prepared separator does not affect the discharge capacity and capacity retention rate of the battery.
[0060] Based on the test results of Examples 1, 6, 7, Comparative Examples 2 and 3, it can be seen that the amount of nano-ceramic composite material powder added during the preparation of para-aramid slurry affects the tensile strength and thermal shrinkage rate of the diaphragm. Furthermore, the tensile strength and thermal shrinkage rate of the diaphragm are optimal when the amount of nano-ceramic composite material powder added is 10-20 kg.
[0061] As can be seen from Example 1 and Comparative Example 4, the tensile strength and thermal shrinkage rate of Example 1 are better than those of Comparative Example 4, indicating that the addition of composite nano-solid materials in this application effectively improves the thermal stability of the separator and effectively reduces the thermal shrinkage of the separator at high temperatures, thereby improving the electrochemical stability of the lithium battery; at the same time, the prepared separator does not affect the discharge capacity and capacity retention rate of the battery.
[0062] Based on the test results of Examples 1, 8, 9, Comparative Examples 5 and 6, it can be seen that the amount of composite nano-solid material added during the preparation of nano-ceramic composite powder affects the tensile strength and thermal shrinkage rate of the diaphragm. Furthermore, the tensile strength and thermal shrinkage rate of the diaphragm are optimal when the amount of composite nano-solid material added is 5-10 kg.
Claims
1. A para-aramid lithium battery separator, characterized in that: The product includes a para-aramid slurry and a base film. The para-aramid slurry is coated on both sides of the base film to form a para-aramid coating. The para-aramid slurry includes the following raw materials in parts by weight: 20-40 parts of modified para-aramid polymer liquid, 10-20 parts of nano-ceramic composite material powder, and 10-18 parts of solvent. The nano-ceramic composite material powder comprises the following raw materials in parts by weight: 50-100 parts of nano-alumina, 8-12 parts of nano-zirconia, 0.3-0.8 parts of yttrium trioxide, 1-5 parts of magnesium nitrate hexahydrate, 0.1-1 parts of polyacrylic acid, 1-2 parts of ammonia, 1-3 parts of coupling agent, and 20-30 parts of silicon dioxide.
2. The para-aramid lithium battery separator according to claim 1, characterized in that: The preparation method of the nano-ceramic composite material powder includes the following steps: Nano-zirconia, magnesium nitrate hexahydrate, polyacrylic acid, and yttrium oxide were mixed, and then nano-alumina was added and mixed again. Ammonia water was added and mixed, centrifuged, and dried to obtain powder. The powder is calcined once to obtain the powder material; The powder is calcined a second time; After the powder was calcined twice, it was mixed with silica and a coupling agent, centrifuged, and dried to obtain nano-ceramic composite material powder.
3. The para-aramid lithium battery separator according to claim 2, characterized in that: When the powder is calcined once, the calcination temperature is 1100-1400℃ and the calcination time is 1-3 hours; When the powder is calcined a second time, the calcination temperature is 1500-1700℃ and the calcination time is 1.5-3.5 hours.
4. The para-aramid lithium battery separator according to claim 2, characterized in that: Before the powder is calcined a second time, it is placed at 180-220MPa for 5-15 minutes and then pre-calcined at 1000-1200℃ for 0.5-1.5 hours.
5. The para-aramid lithium battery separator according to claim 1, characterized in that: The nano-ceramic composite material powder also includes 5-10 parts by weight of composite nano solid materials.
6. The para-aramid lithium battery separator according to claim 5, characterized in that: The composite nanomaterial comprises the following raw materials in parts by weight: 15-20 parts of tetraethyl orthosilicate, 6-13 parts of ethanol, 1-5 parts of hydrochloric acid, and 0.1-1 parts of zirconium oxychloride.
7. The para-aramid lithium battery separator according to claim 6, characterized in that: The preparation method of the composite nano-solid material is as follows: Tetraethyl orthosilicate, a first portion of ethanol, and hydrochloric acid are mixed, zirconium oxychloride and a second portion of ethanol are added and mixed, and then dried to obtain the composite nano-solid material.
8. The para-aramid lithium battery separator according to claim 7, characterized in that: The mass ratio of the first part of ethanol to the second part of ethanol is (5-10):(1-3).
9. The para-aramid lithium battery separator according to claim 1, characterized in that: The preparation method of the modified para-aramid polymer liquid is as follows: terephthaloyl chloride, p-phenylenediamine and a third monomer in a molar ratio of 10:(3-7):(3-7) are co-dispersed in a composite solvent and reacted to obtain the modified para-aramid polymer liquid. The third monomer comprises 4,4'-diaminodiphenyl ether and adipate diamine; the molar ratio of 4,4'-diaminodiphenyl ether and adipate diamine is (6-7):(3-4). The composite solvent includes a chlorinated (1-butyl-3-methylimidazolium) ionic liquid; the volume percentage of the chlorinated (1-butyl-3-methylimidazolium) ionic liquid is 13-18% of the total volume of the composite solvent.
10. A method for preparing a para-aramid lithium battery separator, characterized in that: The preparation method steps are as follows: Weigh out each ingredient according to the formula; Modified para-aramid polymer liquid, nano-ceramic composite material powder, and solvent are mixed to obtain para-aramid slurry. The para-aramid slurry is then coated on both sides of the base film. After coagulation, washing, and drying, the para-aramid lithium battery separator is obtained.
Citation Information
Patent Citations
Method for preparing nanometer alumina-coated zirconium oxide (8 mol.% Y2O3) composite ceramic powder
CN103755342A
High-temperature-resistant lithium battery diaphragm and preparation method thereof
CN116417757A
Para-aramid coating diaphragm and preparation method thereof
CN119764743A
Aramid diaphragm for lithium battery and preparation method of aramid diaphragm
CN119852643A
Strong-acidity composite metal oxide catalyst as well as preparation and application thereof
CN120169342A
Cited By
SiOaramid fiber composite diaphragm as well as preparation method and application thereof
CN122315253A